Capital Structure Determinants: Evidence from Manufacturing and Services Sector Companies in Sri Lanka - Buvanendra, S. (Asian Accounting and Auditing Advancement, 2013)
This paper develops a preliminary study to explore the determinants of capital structure of Sri Lankan listed manufacturing and services sector companies using firm-level panel data for the period of 2003 – 2007. Profitability, Tangibility, Size, and Growth rate were used as independent variables, while leverage ratios such as total debt ratio, long-term debt ratio, and short-term debt ratio were the dependent variables.OLS dummy regression model was used here. The results revealed that only the profitability variable was statistically significant with leverage ratios (with total debt ratio and short-term debt ratio) at manufacturing companies. Meanwhile, all the selected variables, except tangibility were significantly related to at least one of the leverage ratios in services companies. The results of this study validate the prediction of pecking order theory in the case of profitability variables in both manufacturing and services companies. Also growth variable of services companies again confirms the pecking order hypothesis. However size variable of services companies confirms to the prediction of trade-off and agency cost theory.